Organisational perception of critical success factors in green warehouse and inventory - Cheah, Shu Wen (2023)
Green warehouses play a vital role in promoting sustainable practices in the supply chain industry. This paper describes the critical success factor in green warehouse and inventory management. This research aims to determine the critical success factors that contribute to implementing and maintaining a green warehouse and inventory management in the manufacturing industry. Next, it also measures the level of the success factors of a green warehouse and inventory management in the manufacturing industry. A structured questionnaire was used for primary data collection, and statistical tools like descriptive statistics, normality, reliability and factor analysis were used for data analysis. The focused factors will be customer focus, supplier quality management, and Third-Party Logistics (3PL). The respondents were selected based on a population of 150 and a sample size 110, representing the Malaysian manufacturing industry. These samples are related to working experience, job position and sector of manufacturing. Apart from the items investigating the critical success factors in the green warehouse and inventory, all measures were assessed by using a scale from 1 to 5 ranging from “strongly disagree” (1) to “strongly agree” (5). Overall, the result showed that all the respondents positively perceived the questionnaire. In terms of theoretical contribution, this study can inspire future research and contribute to the ongoing discourse on sustainable business practices. Lastly, the practical contribution is to provide valuable insights into the critical success factors and achieve sustainable warehouse and inventory management in the manufacturing industry in Malaysia